PEMBERDAYAAN MASYARAKAT MELALUI AGROWISATA DALAM MENINGKATKAN PEREKONOMIAN DI DUSUN PAMULIAN DESA WARUNGPRING - Mohammad Affan Wijaya; SITI ROBIAH; Khofifah Azzahro; Muhammad Taufiq Ubaidillah; Fitrotul Faizah; Mochammad Najmul Afad; Abdul Basid (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
In the era of globalization and rapid economic development, community empowerment is one of the main focuses in efforts to improve people's welfare. Assets refer to resources that can be used as capital to achieve economic goals, one of the aspects that are in Pamulian Hamlet is Welut Putih Pamulian Agrotourism. The purpose of this study is to analyze more deeply related to community empowerment through agro-tourism in improving the economy in Pamulian Hamlet, Warungpring Village. This research method uses a qualitative approach with data collection techniques through interviews. Data processing in this study uses data validation techniques. The results of this study indicate that Pamulian Welut Putih Agrotourism has an impact on improving the economy of the people in the Pamulian hamlet in Warungpring Village.